Age‐Related Involutory Changes in Bursa of Fabricius of Anas crecca: Histomorphometric and Ultrastructural Investigation - Zeinab Abdel‐Fattah; Ahlam Mostafa El‐Bakry; Abdelaziz S. A. Abuelsaad; Ayman M. Abdel‐Aziz; Ezzat M. Awad; Hossam Ebaid; Rasha E. H. Abo‐Eleneen (Veterinary Medicine and Science)
ABSTRACT Bursa of Fabricius (BF) is a primary lymphoid organ in birds, crucial for lymphocyte development and immune function. This study investigates age‐related alterations in the histomorphology and ultrastructure of the bursal tissue in green‐winged teal (Anas crecca) at 8th and 24th weeks of age. Twenty ducks were examined, and the sample tissues were collected post‐euthanasia for histological and scanning electron microscopy (SEM) analyses. At the 8th week, the histological sections exhibited normal lymphocyte distribution and structural organization, characterized by a well‐developed muscular layer and plicae. In contrast, by the 24th week, significant involution was observed, marked by reduced bursal weight, diminished muscular layer and increased fibrosis. Histological changes included necrosis and depletion of lymphocytes, alongside alterations in the follicular‐associated epithelium. SEM revealed collagen fibre spreading and loss of microvilli, indicating advanced involution. This study highlights the developmental and involutionary stages of the organ in A. crecca, providing essential insights into the age‐dependent changes in this critical immune organ. This is the first report detailing these histomorphometric and ultrastructural alterations in A. crecca, highlighting the age‐dependent nature of these changes, besides contributing to our understanding of avian immunology.